Determination of Morphologic Characteristics of Wild Type Sunflower (Helianthus spp.) Genotypes - Kübra Doğan Tosun; Nazan Dağüstü (Turkish Journal of Agriculture: Food Science and Technology)
The studies were carried out to determine some morphologic characteristics of different wild type sunflower (Helianthus spp.) genotypes at Uludağ University, Faculty of Agriculture Department of Field Crops’ laboratory, green house and field conditions in 2017 and 2018. The 20 wild sunflower genotypes [H. annuus (1, 3, 4, 6, 8, 11, 13, 15, 16, 17, 23, 25, 26, 28), H. argophyllus (34 and 35). H. maximiliani (45), H. petiolaris subsp. fallax (50), H. petiolaris subsp. petiolaris (54) and H. annuus ssp. lenticularis (61)] obtained from USDA-America were used in the study. The highest and lowest average the plant height, the head diameter, the number of branches, stem thickness, the length of petiole and 1000 kernel weight values of some of the morphologic characteristics observed and measured in field conditions during two years changed respectively between 235.0-252.5 cm and 64.0-63.0 cm, 7.1-6.5 cm and 1.9-1.9 cm, 30.8-29.8 number and 11.8-8.1 number, 2.9-3.3 cm and 0.8-0.7 cm, 11.8-11.1 cm and 3.1-0.4 cm, 14.8-14.6 g and 5.6-0.8 g in 2017 and 2018. The characters e.g. the ray and disk flower color, head angle and shape, uniformity of flowering and maturity, bract shape, pollen fertility, pubescence at general appearance, branching and type of branching did not show clear differences within genotypes in two years.